Combined polyphenols in Psidium guajava-citrus limon leaf extract attenuate fructose-induced cardiac injury by modulating metabolic and oxidative stress pathways in rats - Hend A. Essa; Dina E. ElMosbah; Heba A. Fahmy (PLoS ONE, 2026)
Background High fructose consumption is associated with metabolic and cardiovascular dysfunction. Polyphenol-rich lemon and guava leaves may protect the heart. Objective This study investigated the protective effects of Citrus limon leaf extracts, individually and in combination with Psidium guajava , against high fructose-induced cardiac injury in rats. We hypothesized that the polyphenol-rich extracts would attenuate cardiac damage through metabolic and oxidative stress modulation, with synergistic enhancement in the combined treatment. Methods The chemical composition of lemon and guava leaves was analyzed using LC-ESI-MS/MS, along with total phenolic, flavonoid, and antioxidant assays. Male Sprague-Dawley rats (n = 6/group) were divided into: a control group, a fructose group (20% w/v in drinking water for 6 weeks), and two treatment groups receiving either lemon leaf extract (200 mg/kg/day) or a lemon-guava leaf extract (200 mg/kg/day, 1:1) for 2 weeks, followed by co-administration with fructose for 6 weeks. Blood glucose, insulin, lipid profiles, troponin I, creatine kinases, oxidative stress markers, and inflammatory markers were measured. Histopathological and immunohistochemical analyses were performed. Results Sixteen phenolic compounds were identified, with the combined extract showing higher phenolic and flavonoid content and antioxidant activity. Both extracts significantly (p ≤ 0.05) improved insulin resistance and dyslipidemia, significantly (p ≤ 0.05) reduced troponin I and creatine kinase-myocardial band levels, and significantly (p ≤ 0.05) enhanced cardiac antioxidant activity by increasing glutathione, glutathione peroxidase, superoxide dismutase, and catalase, while decreasing malondialdehyde, interleukin-6, and tumour necrosis factor-α. The lemon-guava extract upregulated SIRT1 and NRF2 expression, demonstrating superior efficacy in mitigating fructose-induced cardiac stress. Conclusion The combined lemon-guava leaf extract alleviates fructose-induced cardiac stress, demonstrating potential as a plant-based therapeutic agent for metabolic and cardiovascular protection.